E-HEALTH PERSONAL DATA PROTECTION IN INDONESIA - Hendra Hendra; Ravel Ravel; Novel Firdhaus; Michael Ari Kurniawan; Gilbert Platina (Masyarakat Hukum Kesehatan Indonesia, 2022)
Since Covid-19 day by day users additional attentive to their privacy and information protection. though this drawback is transverse to each digital service, it's particularly relevant once important and private info is managed, as in eHealth and well-being services. throughout the last years, many alternative innovative services during this space are projected. However, information management challenges area unit still in would like of an answer. In general, information area unit directly sent to services however no trustworthy instruments to recover this information or take away them from services area unit obtainable. In these paper author needs to debate privacy aspects of non-public information within the eHealth program and the way Indonesia regulate Privacy and protection of patient’s personal information in Indonesia. the strategy used is normative juridical approach with descriptive analytical specifications. the method of knowledge assortment is finished through literature.